DISPUTA NO TERRITÓRIO: ANÁLISE DO DISCURSO CRÍTICA DA COBERTURA JORNALÍSTICA DO GAZETA ONLINE (2017-2019) SOBRE O PARQUE TECNOLÓGICO DE VITÓRIA - Brito, Mayra Belem Tavares de (2022)
Since the early 1990s, Victoria (Espirito Santo, Brazil) has been discussing the installation of a technology park that, according to its supporters, will bring greater dynamism to the local economy. However, the venture has not yet materialized, configur